LEGAL ANALYSIS OF BREACH OF PROMISE (BREACH OF PERFORMANCE) IN THE DECISION OF THE RANTAUPRAPAT DISTRICT COURT NUMBER 9/Pdt.GS/2022/PN RANTAUPRAPAT - Raja Achmad Parluhutan Rambe; Andryan Andryan (Inspiring Law Journal, 2026)
This study examines the application of civil law to a case of default in the Rantauprapat District Court Decision Number 9/Pdt.GS/2022/PN Rantauprapat. The research method uses a normative juridical approach with literature review and decision analysis. The results show that the judge has applied the provisions of the Civil Code, specifically Articles 1243 and 1250, by imposing a debt repayment obligation, a 6% per annum moratorium interest, and seizing collateral on the defendant's assets. This decision reflects legal protection for creditors and the application of the principle of pacta sunt servanda. However, obstacles to the execution of the decision and the slow judicial process remain major obstacles. This study recommends improving regulations related to the execution of decisions and the application of dwangsom to ensure legal certainty.